Biodiversity assessment in Western Mediterranean marine protected areas (MPAs): Porifera of Posidonia oceanica meadows (Asinara Island MPA) and marine caves (Capo Caccia–Isola Piana MPA) of Sardinia. Issue 1 (1st January 2018) - Padiglia, A.; Cadeddu, B.; Ledda, F. D.; Bertolino, M.; Costa, G.; Pronzato, R.; Manconi, R.
Abstract: This paper focuses on a faunistic inventory and the biogeographic pattern of Sardinian Porifera in a scarcely investigated Italian sea belonging to the Eastern Algero-Provençal Basin. The composition and structure of sponge fauna were studied in two priority habitats in two Marine Protected Areas (MPAs) of the North-Western Sardinian Sea. Shallow-water surveys investigated Posidonia oceanica meadows at five sites in the Asinara Island MPA and three karstic submerged caves in the Capo Caccia–Isola Piana MPA. The annotated checklist shows notably high values of taxonomic richness, confirming that P. oceanica meadows and karstic caves are key habitats for Porifera assemblages. Indeed, the sponge taxa recorded (n = 77) with 59 cave-dwelling and 45 taxa in seagrass meadows represent over 10% of the total Mediterranean sponge fauna, despite the small areas investigated, restricted biotopes and low sampling effort. This suggests that species richness is underestimated in circum-Sardinia seas. Internationally protected species (n = 6), rare species (n = 5) and Mediterranean endemic species (n = 14) were recorded. Previously investigated Posidonia meadows and caves share comparable values of species richness and endemicity with the Sardinian biotopes. The geographic range of species indicates that the biogeographic affinity of the NW Sardinian Sea sponge fauna is dominated by Atlanto-Mediterranean species. The three caves harbour a notably homogeneous sponge community, as indicated by the ca. 50% of shared species and high similarity index (> 83%). By contrast, the composition varies markedly among the five Posidonia meadows, which share only five species and display similarity values ranging ca. 20–60%. Unexpectedly when comparing these contrasting biotopes, faunal similarity is relatively low (< 40% shared species); indeed, Posidonia meadows harbour a notable number of cave-dwelling species in intermatte shaded microhabitats.